The role of integrated Islamic education towards empowerment of Islamic society: a case study of Malaysian integrated school - Fatah Yasin, Raudlotul Firdaus (Postgraduate Programme, State Institute on Islamic Studies Purwokerto, 2019)
The call for an Integrated Islamic Education has become widely discussed in the modern era, especially within the South Asia region including Malaysia and Indonesia. Among the noble objectives of such a system is to nurture an integrated individual who is well versed in both Islamic Revealed Knowledge or transmitted knowledge (al-‘ulum al-naqliyyah) and rational sciences (al-‘ulum al-‘aqliyyah). By employing qualitative method of research, the paper aims at defining the system and its objectives, identifying its role in empowering the Muslim Society and proposing for the solutions and reconstruction to the challenges faced within the current system. The paper concludes that integrated education should begin as early as childhood in order to ensure a profound fundamental Islamic knowledge within an individual including the memorization and comprehension of Quran and Prophetic hadith (SAW).